Malignant transformation of craniopharyngioma - Virik, Kiran; Turner, Jennifer; Garrick, Raymond; Sheehy, John P (Journal of clinical neuroscience, 1999)
Craniopharyngioma is a well recognised intracranial tumour; malignant transformation has been rarely described. In that case, malignant change occurred following irradiation for local recurrence and information is not provided on the biological behaviour of the tumour or the response to management. We report a further case of malignant transformation in recurrent craniopharyngioma following radiotherapy. The biological behaviour of malignant change in craniopharyngioma is uncertain so the treatment modalities require consideration of toxicity and other adverse sequelae balanced against anticipated outcome and comorbidities from previous treatments. The pathophysiology and therapeutic strategies are discussed. We review the possible pathogenic link between radiation therapy and malignant transformation.